2007
DOI: 10.1007/s10681-007-9357-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved drought tolerance of transgenic Zea mays plants that express the glutamate dehydrogenase gene (gdhA) of E. coli

Abstract: Genetic modiWcation of nitrogen metabolism via bacterial NADPH-dependent glutamate dehydrogenase (GDH; E.C.4.1.2.1) favorably alters growth and metabolism of C3 plants. The aim of this study was to examine the eVect of expression of GDH in the cytoplasmic compartment of Zea mays cells. The gdhA gene from Escherichia coli , that encoded a NADPH-GDH, was ligated to the ubiquitin promoter that incorporated the Wrst intron enhancer and used to transform Z. mays cv. 'H99' embryo cultures by biolistics. R0-R3 genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 41 publications
4
39
0
2
Order By: Relevance
“…In fact, in a previous study, the over-expression of sucrose phosphate synthase, the key enzyme in the sucrose synthesis pathway, improved yield characteristics of potato (Ishimaru et al 2008). e introduction of a fungal or bacterial gdhA gene, encoding NADP(H)-GDH, into crops was useful for improving yields in rice (Abiko et al 2010), maize (Lightfoot et al 2007) and tobacco (Ameziane et al 2000), although increases of photoassimilates were not demonstrated in these previous studies. Given that the harvested parts of potato and tobacco are vegetative organs, while those of rice and maize are reproductive organs, gdhA appears to be a powerful tool to improve the yield of crops, regardless of which organ is harvested for use.…”
Section: Increase Of Photosynthetic Rates and Biomass In Gdh Potatoesmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, in a previous study, the over-expression of sucrose phosphate synthase, the key enzyme in the sucrose synthesis pathway, improved yield characteristics of potato (Ishimaru et al 2008). e introduction of a fungal or bacterial gdhA gene, encoding NADP(H)-GDH, into crops was useful for improving yields in rice (Abiko et al 2010), maize (Lightfoot et al 2007) and tobacco (Ameziane et al 2000), although increases of photoassimilates were not demonstrated in these previous studies. Given that the harvested parts of potato and tobacco are vegetative organs, while those of rice and maize are reproductive organs, gdhA appears to be a powerful tool to improve the yield of crops, regardless of which organ is harvested for use.…”
Section: Increase Of Photosynthetic Rates and Biomass In Gdh Potatoesmentioning
confidence: 92%
“…Leaf biomass increased in tobacco upon over-expression of the gdhA gene from Escherichia coli (Ameziane et al 2000). In Zea mays, over-expression of the E. coli gdhA gene improved drought tolerance and increased the yield in dry conditions (Lightfoot et al 2007). In another study, over-expression of the gdhA gene from Aspergillus nidulans altered the concentrations of some free amino acids in fruits of transgenic tomato plants (Kisaka and Kida 2003).…”
mentioning
confidence: 99%
“…While photosynthesis can be maintained under fl uctuations of water supply (Lightfoot et al 2007 ), water defi cit can alter the C and N transformations by bringing about changes in the soil-microbe interactions such as reducing the activity of nitrifying bacteria (StClair and Lynch 2010 and references therein). This is evident from the inhibition of nitrogen fi xation in legume crops during C and N fl uxes under drought (Ladrera et al 2007 ;Rogers et al 2009 ).…”
Section: N In Water and Salt Stressmentioning
confidence: 99%
“…As one of the cheapest agricultural inputs ($US200-400 per ha) in many countries, N fertilizer is often applied in excess of crop needs. Since many crops are heavily fertilized directly or from the rotational crop residue, high NUE during high soil concentrations is the metric commonly often targeted for improvement by breeders and biotechnologists in this field (Lightfoot et al 2001(Lightfoot et al , 2007Lightfoot 2008Lightfoot , 2009. Enhanced NUE by plants should enable crops to be cultivated under reduced N availability, with slow release fertilizers, under water and biotic stress conditions, or poor soil quality.…”
Section: General Conceptsmentioning
confidence: 99%